Evaluation of Salicornia Bigelovii Oil Planted Under Different Treatments: A Comparative Analysis - El-Araby, R.; Rezk, A. I.; El-Enin, S. A. Abo; Nofal, O. A.; El-Nasharty, A. B. (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
The percentage of oil in a representative sample of Salicornia Bigelovii seeds was assessed using different extraction methods using some organic solvents to find the most cost-effective one, and the effect of S. Bigelovii cultivation under different irrigation and fertilisation conditions on the percentage, composition, and nutrition value of oil was determined. From the International Training Centre-Mariut, Alexandria, we got representative samples of Salicornia Bigelovii seeds which are collected from the seacoast and 17 samples of S. Bigelovii seeds which are subjected to different treatments of irrigation and fertilization. The oil percent in a blank sample (B) was calculated using various solvents (hexane, hexane-isopropanol, and ethanol) and methods (shaker, conventional, and ultrasonic). The ultrasonic probe technique evaluated oil% in 17 samples using ethanol. GC analysis was used to determine the oil composition. The phenolic and flavonoid contents in the residue were determined by the Folin-Ciocalteu reagent and colorimetric method, respectively. We focused this research on the effect of Salicornia Bigelovii cultivation under different conditions of irrigation and fertilization on both the percentages and fatty acids composition of the oil. The capability of this oil is to produce biofuel and finally for nutritional, cosmeceutical, and pharmaceutical applications. The characterizations of samples will compare with blank samples that were collected from the desert coastal area of the saline aquatic environment.